Consumers’ Preference for Dried Fish with Emphasis on Packaging in Dhaka city - Towhidul Islam, Md.; Chowdhury, Paromita; Nusrat Jahan, Syeda; Adib Flowra, Fawzia; Tariqul Islam, Md. (Fishery Technology, 2020)
Consumers’ preference for dried fish with emphasis on packaging in Dhaka city was investigated by survey method using a structured questionnaire. A total of 45 consumers (15 in each market) in the open-air retail markets of Dhaka city were selected by purposive sampling technique. Majority of the respondents were male (84%), in the age group of 15-59 years (84%) and having below the Higher Secondary Certificate (HSC) level of education (75%). Most of the consumers (73%) came from the low-income groups. Around 87% like to eat dried fish. Around 53% of consumers buy dried fish weekly, and they spend monthly on an average of 370 BDT. More than 90% of consumers preferred to consume dried fishes with satisfaction on the existing quality. However, 96% of consumers also showed a willingness to pay 10-15% higher price if packaging and quality are improved. Based on the consumers’ preferences, this study indicated that there is good potential for quality packaged dried fishes, which is readily accessible and affordable for the consumers.